Intact myocardial preparations reveal intrinsic transmural heterogeneity in cardiac mechanics. (April 2020) - Pitoulis, Fotios G.; Hasan, Waseem; Papadaki, Mary; Clavere, Nicolas G.; Perbellini, Filippo; Harding, Sian E.; Kirk, Jonathan A.; Boateng, Samuel Y.; de Tombe, Pieter P.; Terracciano, Cesare M.
Abstract: Determining transmural mechanical properties in the heart provides a foundation to understand physiological and pathophysiological cardiac mechanics. Although work on mechanical characterisation has begun in isolated cells and permeabilised samples, the mechanical profile of living individual cardiac layers has not been examined. Myocardial slices are 300 μm-thin sections of heart tissue with preserved cellular stoichiometry, extracellular matrix, and structural architecture. This allows for cardiac mechanics assays in the context of an intact in vitro organotypic preparation. In slices obtained from the subendocardium, midmyocardium and subepicardium of rats, a distinct pattern in transmural contractility is found that is different from that observed in other models. Slices from the epicardium and midmyocardium had a higher active tension and passive tension than the endocardium upon stretch. Differences in total myocyte area coverage, and aspect ratio between layers underlined the functional readouts, while no differences were found in total sarcomeric protein and phosphoprotein between layers. Such intrinsic heterogeneity may orchestrate the normal pumping of the heart in the presence of transmural strain and sarcomere length gradients in the in vivo heart. Graphical abstract: Unlabelled Image Highlights: The myocardial slice preparation is an intact cardiac model allowing the study of transmural properties. Mechanical behaviour is cardiac layer dependent. Structural differences in cardiomyocyte density, orientation, and aspect ratio may contribute to these findings.